2002
DOI: 10.1097/00054725-200205000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Granuloma in Crohn's Disease

Abstract: Crohn's disease (CD) is diagnosed from information obtained clinically, pathologically, and radiologically. One important pathologic finding is a granuloma, which is helpful when a positive diagnosis of CD will affect treatment. Whether the presence of a granuloma has any clinical implication is not clear. We conducted a retrospective study to determine whether a granuloma found on a biopsy sample is associated with disease severity, fistulizing or perianal disease, frequent relapses, and extraintestinal manif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
42
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 25 publications
3
42
1
2
Order By: Relevance
“…9 Failure to induce disease by immunization with intestinal autoantigens and murine models of cytokine gene knock-out dsyregulation suggests that CD is a T H 1 immune-mediated imbalance perhaps caused by a delayed-type hypersensitivity against intestinal flora. High-dose immune ablative therapy and HSCT may reset the immune balance resulting in regeneration of a normal phenotype and prolonged disease remission.…”
Section: Resultsmentioning
confidence: 99%
“…9 Failure to induce disease by immunization with intestinal autoantigens and murine models of cytokine gene knock-out dsyregulation suggests that CD is a T H 1 immune-mediated imbalance perhaps caused by a delayed-type hypersensitivity against intestinal flora. High-dose immune ablative therapy and HSCT may reset the immune balance resulting in regeneration of a normal phenotype and prolonged disease remission.…”
Section: Resultsmentioning
confidence: 99%
“…In an early paediatric cohort, 18 including 56 CD patients, presence of epithelioid granulomas (33% of patients) was associated with a greater likelihood of ileal involvement, perineal disease, and surgery for CD. A more recent study 66 of 82 prevalent CD cases found no difference between patients with (26%) and without epithelioid granulomas regarding the number of patients with extraintestinal CD manifestations, perineal disease, and/or fistulas; among 82 patients, 42 were followed up for longer than one year, and neither the number nor the severity of CD flares during the period differed between the two groups. Finally, two studies evaluated the significance of histological findings as predictors of CD outcome; one sought to identify histological features distinguishing patients with penetrating or stricturing CD lesions from those without complications 67 and another looked for histological patterns predicting relapse of ulcerative colitis.…”
mentioning
confidence: 83%
“…23 The granuloma has long been considered as a histologic hallmark for CD, which is identified between 9% and 60% of patients with CD. [24][25][26][27][28] The prognostic significance of the granuloma remains unknown although many investigators have attempted to link the presence of granulomas with postoperative recurrence 29 and disease severity. 27,28 However, the association between the presence of granulomas and the recurrence of CD remains controversial.…”
mentioning
confidence: 99%
“…[24][25][26][27][28] The prognostic significance of the granuloma remains unknown although many investigators have attempted to link the presence of granulomas with postoperative recurrence 29 and disease severity. 27,28 However, the association between the presence of granulomas and the recurrence of CD remains controversial. [29][30][31][32][33] The association between surgical pathology markers and postoperative recurrence in CD has been investigated.…”
mentioning
confidence: 99%